A density functional theory study of the synthesis of 3-phospholene oxide through the McCormack cycloaddition reaction. (7th November 2020) - Lashkari, Sabrieh; Shahraki, Mehdi; Darijani, Mahdieh; Mahmoudi, Fatemeh
Abstract: The [4 + 2] cycloaddition reaction (McCormack reaction) of 1, 3-butadiene with dichloromethylphosphine (DCMP) yielding 3-phospholene oxide has been studied by density functional theory (DFT) at the M06-2x/6-311++G(2d, 2p) computational level. This reaction is a cheletropic process that comprises two steps with the formation an ionic intermediate in the first step and subsequently, its hydrolysis, in the second step. For the first step of this reaction, three paths were considered as a stepwise pathway with a diradical intermediate and an assumed path with a trigonal intermediate that compared with the concerted path in terms of energy. Analysis of the reactivity indices showed that the 1, 3-butadiene and DCMP behaved as nucleophile and electrophile, respectively. Graphical abstract: